2014
DOI: 10.1186/1471-2393-14-314
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in prepregnancy BMI and impact on maternal and neonatal outcomes and postpartum weight retention: the EFHL longitudinal birth cohort study

Abstract: BackgroundLong-term obesity after pregnancy is associated with obesity prior to pregnancy and retention of weight postpartum. This study aims to identify socioeconomic differences in prepregnancy body mass index, quantify the impact of prepregnancy obesity on birth outcomes, and identify determinants of postpartum weight retention.MethodsA total of 2231 pregnant women, recruited from three public hospitals in Southeast Queensland in Australia during antenatal clinic visits, completed a questionnaire to elicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 44 publications
0
45
1
3
Order By: Relevance
“…The characteristics of included studies are summarized in Table . Most were conducted in the USA , with some in Europe , Australia and one in Canada . Sample characteristics were reported infrequently; of 20 included studies, 13 reported participant ethnicity or race , 9 reported mean age and 5 reported mean BMI .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included studies are summarized in Table . Most were conducted in the USA , with some in Europe , Australia and one in Canada . Sample characteristics were reported infrequently; of 20 included studies, 13 reported participant ethnicity or race , 9 reported mean age and 5 reported mean BMI .…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings of prolonged labour was reported in previous studies. 21,[29][30][31] The mean (SD) birth weight was found to be higher in cases when compared to controls (3.2 (±0.86) vs 2.9 (±0.28)) (p = 0.07). Other studies have found out similar higher incidence of macrosomia.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos prévios demonstraram múltiplos fatores associados à retenção de peso pós-parto (RPPP). Dentre eles, destacam-se o elevado ganho de peso gestacional (GPG) 7,8,9 , a menor idade 10,11 , a primiparidade 12,13 , o menor intervalo interpartal 14 , a pouca prática de atividade física 15 e a menor duração de aleitamento materno 15,16 . Entre os fatores citados, o GPG tem sido identificado como um dos principais determinantes.…”
Section: Introductionunclassified